An overview of students’ entrepreneurial intention antecedents - Gabbianelli, Linda; Bonfanti, Angelo; Loza Adaui, Cristian R.; Mion, Giorgio (Piccola Impresa / Small Business, 2021)
This paper provides an overview of antecedents of the students’entrepreneurial intention (SEI). A selection, collection,analysis, and systematization of previous studies wascarried out to update and reorder the available literatureabout factors influencing SEI. The analysis reveals the followingthree sets of antecedents of SEI: 1) factors relatedto personality traits, 2) contextual/situational factors and3) factors related to personal background. In addition, thisstudy highlights specific theoretical models used to investigatefactors influencing students’ intention to start a newbusiness, such as the theory of planned behaviour model,the entrepreneurial event model and the social cognitivetheory. These results contribute to organising the currentstate of knowledge about the antecedents of SEI and addressingfuture research by providing a spectrum of variablesthat can act as a base to develop further analyticalmodels and theoretical constructs about this topic.